Distribution and risk of the second discordant primary cancers combined after a specific first primary cancer in German and Swedish cancer registries. Issue 1 (1st December 2015) - Chen, Tianhui; Fallah, Mahdi; Jansen, Lina; Castro, Felipe A.; Krilavicuite, Agne; Katalinic, Alexander; Eisemann, Nora; Emrich, Katharina; Holleczek, Bernd; Geiss, Karla; Eberle, Andrea; Sundquist, Jan; et al.
Highlights: We used huge databases (covering 27 million Germans and 9 million Swedes). We found elevated risk of SDPCs combined after 19 cancers in both countries. Our data suggest common etiology of SDPCs after most of first primary cancers. Our data suggest similar registration practices for most SDPCs in both countries. Decreased risk after fatal cancers in Germany may be due to reporting practices. Abstract: We aimed at investigating the distribution and risk of all second discordant primary cancers (SDPCs) after a specific first primary cancer in Germany and Sweden to provide etiological understanding of SDPCs and insight into their incidence rates and recording practices. Among 1, 537, 004 survivors of first primary cancers in Germany and 588, 103 in Sweden, overall 80, 162 and 32, 544 SDPCs were recorded, respectively. Standardized incidence ratios (SIRs) of all SDPCs were elevated at levels between 1.1 and 2.1 after 23 (out of overall 29) cancers in Germany and at levels between 1.1 and 1.6 after 24 cancers in Sweden, and among them, elevated SIRs were found after 19 cancers in both populations. Decreased SIRs at levels ranging from 0.5 to 0.9 were found for some cancers with poor prognosis in Germany only. We found elevated risk after 19 out of 29 cancers in both countries, suggesting common etiology of SDPCs after most of first cancers and registration similarity. Decreased risks after some fatal cancers were found only in Germany, which may be attributed to reporting practices or missed death data in Germany.